Epidemiology of Dermatophytes Among Primary School Children in Calabar, Nigeria - Ekomobong A. Okpo; Iniobong E Andy; Godwin E John; Rosemary C. Chinyeaka (Health for All Nations, 2024)
Background & Aims: Children are more susceptible to dermatophytes due to different predisposing factors, such as under developed immune system and high sensitivity of their skin to infection. This study investigated the epidemiology of dermatophyte infection among primary school children in Calabar municipality, Nigeria. Methods: Students attending two primary schools, DPS and PCNPS in Calabar Municipality, were clinically screened. Samples were collected from children with physical signs of dermatophytes on skin, scalp, and nails, and who were present on the day of sample collection. Affected areas were scraped and swabbed. Cultures were done on SDA, and Lactophenol cotton blue was used to prepare isolates for microscopy. Results: A total of 779 children aged 4-17 years were screened. 202(25.9%) were mycologically positive by culture. The occurrence of dermatophyte infection was significantly higher in young children aged 4-6 years than in older children. Male children were more frequently infected (17.6%) than females (8.3%). Trichophyton spp. was the most prevalent etiological agent (35.6%), followed by Microsporum spp. (31.7%), and Epidemophyton spp. (19.3%). Plates with mixed colonies constituted 13.4% of the entire culture. Dermatophytes were mostly isolated from the scalp (63.9%), followed by skin (32.2%), and nails (4%). The prevalence of dermatophyte infection among the two schools' children was 32.0% and 21.9% in DPS and PCNPS, respectively. Conclusion: Dermatophyte infection is still prevalent among primary school children. Regular screening and use of educational health awareness of dermatophyte infection are recommended.